Non-native vascular flora of the Arctic : Taxonomic richness, distribution and pathways - Wasowicz, Pawel; Sennikov, Alexander N.; Westergaard, Kristine B.; Spellman, Katie; Carlson, Matthew; Gillespie, Lynn J.; Saarela, Jeffery M.; Seefeldt, Steven S.; Bennett, Bruce; Bay, Christian; Ickert-Bond, Stefanie; Väre, Henry (Ambio, 2020)
We present a comprehensive list of non-native vascular plants known from the Arctic, explore their geographic distribution, analyze the extent of naturalization and invasion among 23 subregions of the Arctic, and examine pathways of introductions. The presence of 341 non-native taxa in the Arctic was confirmed, of which 188 are naturalized in at least one of the 23 regions. A small number of taxa (11) are considered invasive; these plants are known from just three regions. In several Arctic regions there are no naturalized non-native taxa recorded and the majority of Arctic regions have a low number of naturalized taxa. Analyses of the non-native vascular plant flora identified two main biogeographic clusters within the Arctic: American and Asiatic. Among all pathways, seed contamination and transport by vehicles have contributed the most to non-native plant introduction in the Arctic. Peer reviewed